The Use of Code Mixing by The Javanese People in Gerokgak Village - Ilham Renaldi (Lembaga Pengembangan Kinerja Dosen, 2025)
The aim of this research was to analyze the code mixing used by Javanese people in Gerokgak village. The things that were analyzed were the types of code mixing and the reasons for code mixing. The types of code mixing used the theory of (Suwito, 1983) and the reasons for code mixing used the theory of (Hoffmann, 1991) and interviews. This research method was qualitative descriptive. Data collection used observation and interview techniques, then for data analysis techniques used the theory of (Milles & Huberman, 1994). Based on the results of the study, the types of code mixing that occurred were inner code mixing and outer code mixing. The inner code mixing was the dominant type that contained 56 data and the outer code mixing contained 37 data. The reasons for code mixing obtained were Talking about particular topics contained 71 data, being emphatic about something contained 3 data, interjection contained 1 data, repetition used for clarification contained 2 data and expressing group identity contain 19 data. Based on the interview of the participants, reasons they used code mixing were because they live in mixed societies, for daily communication with people, because the community uses different languages, and adjusting to the interlocutor. Based on the results of the study, it can be concluded that code mixing appears in the participants' conversations with various types and reasons.